Changes in the Essential Oil Content and Composition of Thymus daenensis Celak. under Pre-drying and Different Storage Conditions - MR Dehghani Mashkani; H Naghdi Badi; K Larijani; A Mehrafarin (Institue of Medicinal Plants, ACECR, 2018)
Background: The post-harvesting process of medicinal plants such as drying operation and storage conditions has great influence on their quality and quantity of the active ingredients. Objective: The aim of this experiment was to investigate the effect of pre-drying operation and also storage conditions and duration on the essential oil content and composition of Thymus daenensis. Methods: A factorial experiment was conducted based on randomized complete block design with three replications. The first factor include drying operations (including pre-drying and without pre-drying), the second factor include storage method (shade storage and storage in a refrigerator at 4 °C), and the third factor was storage duration (storing the plant's organs for 60, 120 and 180 days). The essential oil was extracted by clevenger apparatus and its components were identified using GC and GC/Mass. Results: The highest amounts of essential oil, linalool, borneol, terpinene-4-ol, thymol methyl ether, e-anethol, thymol and carvacrol were observed in plants stored for 60 days. Also, the highest amounts of α-pinene, camphen, β-pinene, myrcene, α-phellandrene, α-terpinene, limonene, cis-sabinene hydrate and trans-sabinene hydrate were observed in the plants dried in the shade after pre-drying operation and stored in the refrigerator for 120 days. Conclusion: Drying of T. daenensis plants under shade without pre-drying operation and storing in 4 ° C was the best way to obtain the highest amounts of essential oil and its main components (thymol and carvacrol).